Analysis of cell‐type specific exosomes isolated from cryopreserved human brain: Molecular and cell biology/neuroinflammation. (7th December 2020) - Bilousova, Tina; Melnik, Mikhail; Cohn, Whitaker; Huang, Calvin; Teter, Bruce; John, Varghese; Gylys, Karen H.
Abstract: Background: Exosomes are small extracellular vesicles (EVs) originated from multivesicular endosomes which carry biochemical information about their cell‐of‐origin and signals for surrounding cells. EVs may also play a role in spread of proteopathic tau and amyloid beta seeds in Alzheimer's disease (AD). Thus, brain exosomes may be a valuable therapeutic target for AD treatment. Ability of brain exosomes to cross the blood brain barrier make them a potential diagnostic and monitoring tool. Despite recent progress in development of EV isolation methods, our knowledge of human brain exosomal subpopulations and their roles in disease progression is very limited. Method: Cryopreserved parietal cortex from 5 late stage AD (Braak V‐VI) and 3 control (NL) cases were used for the experiment. Brain exosomes/EVs were purified by sucrose density gradient ultracentrifugation after gentle enzymatic and mechanical dissociation of the brain tissue. Microglia‐derived EVs were isolated from the brain EV fraction by immunoprecipitation with anti‐CD11b antibodies. We performed analysis of miRNA transcriptome and proteome using NanoString and quantitative proteomics respectively. Result: We identified 105 miRNAs which are present in more than 80% of analyzed human cases. The pathways controlled by five significantly upregulated miRNAs can be converged to control microglia activation (TGFβ, TLRs, and chemokine signaling pathways) and neuronal survival and function (LTD and LTP, NGF and neurotrophin signaling pathways). One of the upregulated exosomal miRNAs (miR‐188‐5p) is known to be downregulated in human AD brain and it can restore synaptic and cognitive deficits in 5xFAD mice. MiR‐381‐3p can promote recovery of spinal cord injury in rats. On the protein level we found a moderate increase (around 50%) in exosomal markers CD9 and CD81 and decrease in CHMP4B (ESCRT‐III) protein in the AD group. Levels of mitochondrial proteins and annexins were around 2 times higher in AD group compared to NL controls. ApoE protein was also significantly upregulated in AD microglial EVs. Conclusion: Our data revealed the presence of anti‐inflammatory and neuroprotective miRNA signature in CD11b‐positive microglia‐derived exosomes. Proteomics data suggests upregulation of ESCRT‐independent pathway of exosome biogenesis in AD microglia. Increased association of microglial EVs with ApoE maybe related to amyloid packaging and release by exosome‐mediated mechanism.